Slagscener i det elizabethanske teater - Dahl, Christian (Passage - Tidsskrift for litteratur og kritik, 2018)
Christian Dahl: “Battle scenes in the Elizabethan theater” This article analyses the widespread use of staged battle in Elizabethan theater by use of data extracted from Folger Library’s Digital Anthology of Early English Drama. Between 1576 and 1616, hundreds of battle scenes were produced on English stages but although a substantial number is still available for study, only few scholars have recognized their significance. The many battle scenes both attest to the Elizabethans’ vivid interest in history and to the cultural impact of England’s increasing military engagement on the Continent and in Ireland at the end of Elizabeth’s reign. It is often assumed that histories and battle scenes were particularly popular in the 1590’ies and then fell out of fashion early in the 17th century, but the article demonstrates that staged war remained a frequent occurrence in the first two decades of the century and never disappeared entirely. The article discusses visual and, in particular, acoustic representation of warfare based on the evidence of surviving plays and other documents. The article will also (very) briefly sketch the narrative development of battle scenes that took place in the 1590ies.